Pembunuhan Tradisi Peasen - Musa, Farid Th. (Jurnal Pelangi Ilmu, 2008)
Processing of natural resources especially is agricultural sector entangles two different groups oriented to agro product. The difference surrounded by importance to production having usage value and exchange rate in agricultural land processing. This Exchange Rate and usage value differentiates modern traditional agricultural system and agriculture system. Traditional agricultural system is done to fulfill requirement of food, what done by farmer based on knowledge they to correspond to nature ferocity. To fulfill requirement of the food, more opting farmer applies resource which there is around their life. For traditional farmer embracing principle \'ṕrioritizes safing\